The Second World War, Inequality and the Social Contract in Britain. (25th March 2022) - Heldring, Leander; Robinson, James A.; Whitfill, Parker
Abstract : What is the impact of warfare on inequality and the social contract? Using local data on bombing, the evolution of wealth inequality and vote shares for the Labour Party in Britain around the Second World War, we establish two results. First, on average, we find no impact of bombing on inequality. However, there is considerable heterogeneity, and this result is driven by southern Britain. In northern Britain, bombing led to significant falls in inequality. Second, heavier bombing led to a significant increase in the vote share for Labour after the war everywhere, but this effect is transitory in the south while it is permanent in the north. Our results obtain both in a simple difference‐in‐differences framework as well as in a panel‐regression discontinuity framework in which we exploit the limited range of German fighter escort planes. Our results provide novel causal evidence for the inequality‐reducing impact of warfare, and we interpret them as consistent with the notion that the impact of the war also led to a reconfiguration of the social contract in Britain.